Profitability of technical trading systems : evidence in foreign exchange markets - Chan, Elwyn Kah Wai (2008)
In this paper, we present evidence on the profitability of three technical trading systems (TRENDING, NON-TRENDING and COMBINATION) for the USD/JPY currency pair from 3 January 1989 to 15 July 2004.